2019
DOI: 10.1111/jbi.13735
|View full text |Cite
|
Sign up to set email alerts
|

The Magellanic Province and its fish fauna (South America): Several provinces or one?

Abstract: Aim We assessed the validity of the division of the Magellanic Province into the four provinces as proposed by Briggs & Bowen (J Biogeogr 39 12–30, 2012): Southern Chile, Tierra del Fuego, Southern Argentina and Falkland (Malvinas) Islands. We aimed to (a) present an updated list of the fishes from the region known as ‘Magellanic Province’, (b) analyse the specific richness of fishes in the Atlantic and Pacific sectors and their degree of endemism and (c) evaluate statistically the validity of the three Provin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 44 publications
4
15
0
Order By: Relevance
“…Menni et al (2010) also confirmed the two biogeographic provinces based on distribution patterns of chondrichthyans (sharks, rays, and chimaeras). More recently, two studies by Cousseau et al (2019) and Sabadin et al (2020) analyzed updated distribution patterns, richness and endemism of fish and chondrichthyans in the Magellanic Province respectively, corroborating the originally proposed biogeographic units. Note that one study (Briggs and Bowen 2012) has proposed a different biogeographic pattern for the region, but it is currently disregarded because it did not consider previous literature and it was not based on fish distribution data.…”
Section: ₁₇₁ I�����������supporting
confidence: 53%
“…Menni et al (2010) also confirmed the two biogeographic provinces based on distribution patterns of chondrichthyans (sharks, rays, and chimaeras). More recently, two studies by Cousseau et al (2019) and Sabadin et al (2020) analyzed updated distribution patterns, richness and endemism of fish and chondrichthyans in the Magellanic Province respectively, corroborating the originally proposed biogeographic units. Note that one study (Briggs and Bowen 2012) has proposed a different biogeographic pattern for the region, but it is currently disregarded because it did not consider previous literature and it was not based on fish distribution data.…”
Section: ₁₇₁ I�����������supporting
confidence: 53%
“…To delineate endemic areas within the study region, we used multivariate clustering methods (Kreft & Jetz, 2010) to identify geographical clusters of river sub‐basins based on assemblages (sensu Fauth et al., 1996) of freshwater fishes. These methods provide a quantitative and objective first step in identification and delineation of biogeographical regions and have been widely used for aquatic ecosystems (Cousseau et al, 2019; Ennen, Agha, Matamoros, Hazzard, & Lovich, 2016; Ennen et al., 2020; Matamoros et al., 2016; Matamoros, Kreiser, & Schaefer, 2012). First, we performed a hierarchical cluster analysis of the river sub‐basins based on an unweighted pair group method analysis with arithmetic means (UPGMA) on a dissimilarity matrix based on Jaccard index from our presence/absence dataset using the hclust function implemented in the R package ‘vegan’.…”
Section: Methodsmentioning
confidence: 99%
“…To delineate endemic areas within the study region, we used multivariate clustering methods (Kreft & Jetz, 2010) to identify geographical clusters of river sub-basins based on assemblages (sensu Fauth et al, 1996) of freshwater fishes. These methods provide a quantitative and objective first step in identification and delineation of biogeographical regions and have been widely used for aquatic ecosystems (Cousseau et al, 2019;Ennen, Agha, Matamoros, Hazzard, & Lovich, 2016;Ennen et al, 2020;Matamoros et al, 2016;Matamoros, Kreiser, & Schaefer, 2012).…”
Section: Identification Of Fine-scale Biogeographical Structurementioning
confidence: 99%
“…cunninghami , Calliclinus geniguttatus , Piedrabuenia ringueleti ) not previously recorded in this region. Percentage of species endemic to the Magellanic Province was high (60%) when compared to the total endemic species pool in the province (15%) [ 26 ]. According to Cousseau et al [ 26 ], the fish families that best represent endemicity in the Magellanic Province are Nototheniidae and Zoarcidae, which were also the most specious families in our study.…”
Section: Discussionmentioning
confidence: 99%
“…More than 120 fish species have been recorded in the shallow waters (< 20 m) of the southern cone of South America [ 26 , 27 ]. Thirty-five of these fish species have been recorded in association with giant kelp [ 6 , 28 33 ].…”
Section: Introductionmentioning
confidence: 99%